FORMULASI DAN UJI FISIK SALEP KOMBINASI EKSTRAK PUTRI MALU (Mimosa Pudica) DAN DAUN JARAK PAGAR (Jatropha Curcas) - Enjelina, Sinta Mei; Pambudi, Risma Sakti; Ramadhani, Mutia; Subiyanto, Abyasa Fajari; Ilmi, Ibnul; Rahmadin, Mega Tri (Jurnal Buana Farma, 2024)
Indonesia is a tropical country that has the potential to experience skin diseases. The development of drugs from natural ingredients can be used to treat skin diseases. One of the appropriate pharmaceutical preparations for treating skin infections is ointment. Putri Malu (Mimosa Pudica) and Jatropha Leaves (Jatropha Cuscas) are plants that contain flavonoids, alkaloids, saponins, tannins and phenols which have the potential to inhibit bacterial growth. The aim of this research is to formulate an ointment preparation from the extract of putrimalu (mimosa pudica) and jatropha curcas leaves (jatropha curcas) which meets the requirements of an ointment preparation by means of a physical test of the ointment. This type of research was experimental, which was carried out by making 3 ointment formulations combining Putri Malu and Jatropha leaves using the ointment base Vasellin Album and Adeps Lanae. Physically tested ointment preparations include organoleptic tests, homogeneity tests, pH tests, viscosity tests, spreadability tests, and adhesiveness tests. Based on testing of a combination of ointment preparations from the extract of putrimalu (mimosa pudica) and jatropha leaves (jatrooha cuscas) with a base of vasellin album and adeps lanae, the organoleptic results were blackish brown, distinctive odor, semi-solid consistency, homogeneous ointment with a Ph value of 5 and viscosity test. adhesion and spreading power in accordance with ointment preparation standards. The best formulation of the ointment combination of the extract of the mollusk (mimosa pudica) and jatropha curcas (jatropha cusrcas) leaves is formulation 2 with a ratio of (2:2).